Spatial Imagination in Sacred Narratives of Mountain Communities in Western Yunnan, China - Huang, Jinghua (Religions, 2024)
Various sacred narratives have different emphases on the shaping of natural space. Creation myths reveal the basic structure of natural space. Sacred narratives of mountain gods focus on how and why mountain forests are the source of life and stability for nearly all the species in the area. The myth of the hunting god and the legend of the Flower Festival have a remarkable endemicity. The consciousness of the community of life, which is fundamentally constructed in creation myths, reveals visible and sensible pictures in these two types of narratives. The literary imagination of these sacred narratives focuses on establishing and breaking through spatial boundaries. In the intertwining of an imaginative narrative and a realistic existence, the sacredness of natural spaces is established and can be experienced. Mountaineers imbue their practices with gracefulness and nobleness in the dimensions of emotion and morality through storytelling in order to shape the morphological characteristics and the life essence of natural spaces. The shaping of beautiful places and sublime realms in these narratives is a vivid expression of cosmology.